The Faculty of Medicine and the bicentennial of the birth of Hipólito Unanue - Hercelles, Oswaldo (1955)
Upon completion of two hundred years of the birth of Hipólito Unanue, renews the Faculty of Medicine at the foot of bronze perpetuates the memory of the warm feelings of fervent admiration and gratitude that at all times she raised in the illustrious personality of the Father of the Peruvian Medicine Founder of the Medical and Founding father of national independence.